NOCTURNAL SURFACE INVERSIONS IN CENTRAL EASTERN INDIA - PIGGIN , I. G.; ALLEY , S. K. (MAUSAM, 1994)
Monitoring of nocturnal su rface inversions in the vicinit y of Steel Authority of Ind ia lid. Steel plants at Bhila i. Bokaro. Durgapur and Rourk-cia in central eas tern Ind ia. for 40 niahu in January. February and March 1990. indi cated that surface inversions developed every night when weathe r conditions were favourable (clea r skies and light winds) , Th e ceiling heiaht of surface inversions eenerally increased as the niah t progressed. with rouahly two-th irds hiefler th an 100 m and a maximum record ed heigh t of 520 m. Th e maximum recorded surface inversio n strt"ngth (temperature difference between th e surface and the ceilingjwas 8.6C· at Dura:apur.1 .4C· at Bhilai and aroun d 5-SC· at both Bokam and Rourkela. A reaso nable estimate of the .srrongest surface inversion would be JOC· to 12C· in the lOwnl 250 m of th e atmosphere.The proportion of surface invers ions greater than 4C· was 80%at Durgapur. .s5llb at 8hilal4.s% at Bokaro an d If.'" at Rourkela.These differences between loca tion!'wee- caused la l'iel y by varying weathe r conditions during the monit oring period.